(3GdUMGM aj GddZIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s; (3QhGjI CHh eMeO ESeGYjd Hf eMeO GdfjSCHhQis
(3BNQgG (B:s
(3ef aUd GdjGA (B( (3HGH GdQGA (B) (3bhdg (B: (3jYQ hGdjYGQI HGdaJM Cf jMed Ydi GdfGbI GdaMd bGd GdTGYQ GdQGYi (B: - (3bdGFU dG jdMbf EdG jYGQI YQGUkG hdG jTQjf EdG YhGdjG Je GdSaQ GdChd s
(3HgG HYV GdJbWjYs
(3JJab ai ChdgG eY Chd fSNI YGQa MceJ (B- 28 (3dZI HGNJdGa jSjQ LOkG ai HYV GdCdaGX eged GdfbW CMjGfkGs
(3cJHJ GdYfhGfGJ HGdMeQI Ch GdShGOs
(3fSNI SGHYI s
(3JHUQI GdYfhGf (B:s
(3QhGjIs
Keywords: (3GddZIs